Does the stock market value the inclusion in a sustainability stock index? An event study analysis for German firms - Ulrich Oberndorfer; Marcus Wagner; Andreas Ziegler (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
This paper empirically analyzes the effect of the inclusion of German corporations in the Dow Jones STOXX Sustainability Index (DJSI STOXX) and the Dow Jones Sustainability World Index (DJSI World) on stock performance. In order to receive robust estimation results, we apply an event study approach that is based on both a modern asset pricing model, namely the three-factor model according to Fama and French (1993), and additionally on a GARCH model. Our empirical analysis implies that stock markets may penalize the inclusion of a firm in sustainability stock indexes. This result is mainly driven by the negative effect of the inclusion in the DJSI World. While we do not find significant average cumulative abnormal returns for the inclusion in the DJSI STOXX, the inclusion in the DJSI World leads to strong negative impacts. This suggests that the inclusion in a more visible sustainability stock index has larger negative impacts.
Keywords: Q56; M14; G14; G12; C22; 330; sustainability stock indexes; corporate financial performance; event study; three-factor model; GARCH model; Unternehmensentwicklung; Börsenkurs; Nachhaltige Entwicklung; Ethische Geldanlage; Deutschland; Aktienindex; USA